Service Quality of Five Star Hotels in Bangladesh: An Empirical Assessment - Siddique, Md. Nur-E-Alam; Akhter, Mst. Momena; Masum, Abdullah Al (Asian Business Review, 2013)
Although the importance of service quality and service quality measurement have been recognized, there are limited researches that have addressed the structure and antecedents of the concept for the hotel industry in Bangladesh. The clarification of the dimensions of service quality is inevitable for the managers in the hotel industry as these identify the bundles of service attributes consumers find important. Therefore, this study aims to measure the service quality from the customers’ perspective of five star hotels in Bangladesh based on the SERVQUAL model. Three five star hotels (Ruposhi Bangla Hotel, Pan Pacific Sonargaon Hotel, and Radison Water Garden Hotel) out of four were selected for the purpose of the study. The study is based on the primary data collected from the respondents with the help of a self-administered questionnaire to measure the perception of service quality characteristics of the five star hotels. Data analysis has been done using SPSS software and a factor analysis has been conducted to measure the differences among the factors affecting service quality perceptions. To measure the service quality gap, five dimensions related to hotel industry were identified. The analysis shows that the service quality of the five star hotels is highly dependent on the physical appearance, interior decoration, food quality, behavior of the employees, security system, and customized services given to individual customers.